Pemanfaatan Ruang Terbuka Publik Linier Di Kampung Taman Sari Yogyakarta - RATNA DWI MAKSUM (Universitas Gorontalo, 2021)
Taman Sari Village is one of the urban villages in Yogyakarta that still maintains Javanese traditions and culture because the residents in this village are still courtiers of the Yogyakarta Palace. The position of the village which is around the Taman Sari tourist attraction makes this village a tourist area. The condition of the crowded village with narrow roads and alleys but with a beautiful village atmosphere is the image of this village. The majority of linear public open spaces are located in road spaces in the village, so the purpose of this research is to see to what extent the use of linear public open spaces by the people of Kampung Taman Sari is focused on one research location which will be described in three-dimensional detail so that it will be known how the community uses it. space as effectively and efficiently as possible. The research method used is descriptive qualitative. The conclusion of this study is that there are two types of linear public open space utilization in Tamansari Village, namely the utilization of the physical setting and the utilization seen from the activity setting. Utilization of the physical setting for circulation space in the village, on the right and left sides is also used for ecological functions, as well as the placement of information boards and reading boards, as well as places to put trash bins to maintain cleanliness, parking lots for motorbikes, bicycles and parking for rickshaw taxis. Utilization for setting activities in the form of social activities such as playing bicycles for children, being a meeting room for residents with daily activities such as sitting around relaxing and chatting, buying snacks, as a circulation space for example walking, riding bicycles and tricycles, as a place gotong royong such as jointly cleaning the environment together, other activities around linear public open spaces are commercial activities that sell various daily necessities as well as sell food and drinks for tourist visitors who pass through the locationKampung Taman Sari merupakan salah satu kampung kota yang berada di Yogyakarta yang masih mempertahankan tradisi dan budaya jawa karena warga di kampung ini masih abdi dalem Keraton Yogyakarta. Posisi kampung yang berada di sekitar obyek wisata Taman Sari menjadikan kampung ini sebagai kawasan wisata. Kondisi kampung yang padat dengan jalan dan gang-gang sempit namun dengan suasana kampung yang asri menjadi citra dari kampung ini. Ruang terbuka publik linier yang ada mayoritas berada di ruang jalan dalam kampung sehingga tujuan penelitian ini adalah melihat sejauh mana pemanfaatan ruang terbuka publik linier oleh warga Kampung Taman Sari dengan mengambil fokus satu lokasi penelitian yang akan digambarkan secara detail tiga dimensi sehingga akan diketahui bagaimana warga memanfaatkan ruang tersebut secara efektif dan seefisien mungkin. Metode penelitian yang digunakan adalah deskriptif kualitatif. Kesimpulan dari penelitian ini adalah terdapat dua jenis pemanfaatan ruang terbuka publik linier di kampung tamansari yaitu pemanfaatan dari setting fisiknya dan pemanfaatan dilihat dari setting aktivitasnya. Pemanfaatan setting fisik untuk ruang sirkulasi dalam kampung, di sisi kanan dan kiri juga dimanfaatkan untuk fungsi ekologi, serta peletakan papan informasi dan papan baca, serta tempat meletakkan tempat sampah untuk menjaga kebersihan, tempat parkir sepeda motor, sepeda dan parkir ojek becak. Pemanfaatan untuk setting aktivitas berupa kegiatan sosial seperti kegiatan bermain bermain sepeda bagi anak-anak, menjadi ruang pertemuan warga dengan kegiatan harian seperti duduk-duduk sambil santai dan ngobrol, membeli jajanan, sebagai ruang sirkulasi misalnya berjalan kaki, naik sepeda dan becak, sebagai tempat gotong-royong seperti bersama-sama membersihkan lingkungan secara bersama-sama, aktivitas lain yang ada di sekitar ruang terbuka publik linier adalah aktivitas komersial yang menjual aneka kebutuhan untuk sehari-hari maupun menjual makanan dan minuman untuk para pengunjung wisata yang melewati lokasi tersebut